2020
DOI: 10.33752/disastri.v2i1.872
|View full text |Cite
|
Sign up to set email alerts
|

Proses Derivasi Dan Infleksi Dalam Bahasa Indonesia Pada Berita Koran Jawa Pos Radar Jombang Edisi Juli 2019

Abstract: Penelitian ini bertujuan untuk menganalisis tentang pembentukan kata derivasi dan infleksi dalamBahasa Indonesia. Perlu adanya bukti yang konkrit untuk mengetahui keduanya, seperti berita dalam koran,majalah, dan bacaan lainnya. Hal tersebut dikarenakan proses derivasi dan infleksi akan dipahami dalambentuk bacaan bukan hanya teori saja. Penelitian ini menggunakan metode kualitatif. Teknik pengumpulandatanya menggunakan studi pustaka. Adapun yang menjadi objek penelitian adalah proses derivasi daninfleksi, sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Therefore, it is necessary to have concrete evidence to know this process, for example in fiction or non-fiction writing, to news in newspapers. On the other hand, the process of derivation will be more understandable in its application (reading form), not just in theory (Zuhro, 2019). Returning to the concept of derivation, it is classified as a process of forming a word from another lingual unit which becomes a lexeme (Chaer, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to have concrete evidence to know this process, for example in fiction or non-fiction writing, to news in newspapers. On the other hand, the process of derivation will be more understandable in its application (reading form), not just in theory (Zuhro, 2019). Returning to the concept of derivation, it is classified as a process of forming a word from another lingual unit which becomes a lexeme (Chaer, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the results of research conducted by Zuhro (2019) showed that in the formation of a word, apart from following the perspective of derivation and inflection, it also involved several aspects of morphology. These aspects included affixation, reduplication, and morphophonemic so that they were able to produce word forms that could be used in rules of Indonesian words.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian derivasi dan infleksi dilakukan oleh Mata (2021) Abdullah, et. al (2020), Zuhro (2020), Anggraini (2019), Bagiya (2017), dan Ermanto (2016). Hasil penelitian tersebut menjelaskan bahwa derivasi dan infleksi disebabkan oleh proses morfologis salah satunya afiksasi.…”
Section: Pendahuluanunclassified
“…According to Zuhro (2020), the function of derivative affixes is to produce new fundamental forms to which derivative affixes or other inflectional affixes can be added. Several criteria distinguish between derivational and inflectional morphemes.…”
Section: Introductionmentioning
confidence: 99%